Practical Aspects of Cardiopulmonary Exercise Testing in Children - Takken, Tim; Hulzebos, Erik H. (International Journal of Sports Medicine, 2023)
The use of cardiopulmonary exercise testing (CPET) in pediatrics provides critical insights into potential physiological causes of unexplained exercise-related complaints or symptoms, as well as specific pathophysiological patterns based on physiological responses or abnormalities. Furthermore, CPET helps evaluate exercise performance in children with chronic (lung/heart) diseases. For instance, it can ascertain any adverse reaction to exercise and estimate the effects of specific treatment measures. It affords a global assessment of the pathophysiological patterns, responses and abnormalities to exercise that is inadequately reflected by resting lung function and/or cardiac function assessment. Clinical interpretation of the results of a CPET in pediatrics requires specific knowledge regarding pathophysiological responses and interpretative strategies that can be adapted to address concerns specific to the child’s medical condition or disability.
Keywords: physiology; child; exercise test; fitness